Development of Islamic Value-Based Mathematics Teaching Materials to Improve Students' Understanding of Mathematical Concepts - Ani Choirunnisa; Nurhanurawati Nurhanurawati; Syarifuddin Dahlan; Choirudin Choirudin; Muhammad Saidun Anwar (Jurnal Analisa, 2022)
Penelitian ini bertujuan untuk menghasilkan media dalam modul berbasis Islam pada materi Aritmatika Sosial dalam meningkatkan pemahaman konsep matematika siswa. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE. Tahapan yang dilakukan adalah Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Data penelitian diperoleh dengan menggunakan kuesioner, wawancara, dan tes khusus. Hasil penilaian berdasarkan angket validasi ahli materi untuk modul ini termasuk dalam kategori “Valid” dengan skor rata-rata 83%. Penilaian ahli media memperoleh skor rata-rata 87% dalam kategori “Valid”. Pada uji coba lapangan skala besar diperoleh rata-rata 83% dengan kriteria “Menarik”. Kualitas keefektifan produk dilihat dari tes hasil belajar. Hasil analisis data dengan menggunakan uji-t pembelajaran menggunakan modul matematika berbasis Islam yang diterapkan di kelas VII 1 lebih efektif daripada di kelas VII 2 yang pendidikannya tidak menggunakan modul matematika berbasis Islam. Hasil analisis menggunakan N-Gain adalah peningkatan pemahaman konsep matematika siswa. Berdasarkan hasil tersebut dapat disimpulkan bahwa modul berbasis Islam adalah valid (layak), menarik, praktis untuk digunakan sebagai sumber belajar, dan dapat meningkatkan pemahaman konsep matematika siswa.  This study aims to produce media in Islamic-based modules on social arithmetic material in improving students' understanding of mathematical concepts. The study method used is Research and Development (R&D) with the ADDIE development model. The stages carried out are Analysis, Design, Development, Implementation, and Evaluation. The research data was obtained using questionnaires, interviews, and special tests. The assessment results based on a material expert validation questionnaire for this module are included in the "Valid" category with an average score of 83%. The media expert's assessment obtained an average score of 87% in the "Valid" category. In a large-scale field trial, an average of 83% was obtained with the "Attractive" criteria. The quality of the product's effectiveness is seen from the learning outcomes test. The results of data analysis using t-test learning using Islamic-based mathematics modules that are applied in class VII 1 are more effective than in class VII 2, whose education does not use Islamic-based mathematics modules. The analysis results using N-Gain are an increase in students' understanding of mathematical concepts. Based on these results, it can be concluded that Islamic-based modules are valid (feasible), attractive, practical to be used as learning resources, and can improve students' understanding of mathematical concepts.